Karakterisasi Biofilm Selulosa Bakteri dengan Modifikasi Gliserol secara Ex Situ - Panjaitan, Vera Diana; Iriany; Sukeksi, Lilis (Talenta Publisher (Universitas Sumatera Utara), 2024)
Bacterial cellulose (BC) is biomaterial from bacterial fermentation that contain high purity of cellulose, but 90% of BC pellicles retained water from the fermentation process. In this study, BC was modified with glycerol immersion in different concentrations (0%; 2,5%; 5%; 7,5%; 10%). For wide application, water content on BC must be removed by drying. Various oven drying condition are temperature 80 °C and 120 °C and time 60 minutes. The physical and mechanical properties of the dried BC biofilm were determined including tensile strength and elasticity. BC biofilm bound was identified by FTIR and EDX. The results showed that glycerol concentration was able to increase biofilm elasticity from 3.46% to 27.743%. However, glycerol immersion above 7.5% caused a decrease in the tensile strength of BC biofilm. The drying variation of 120 °C produces the highest tensile strength of 7.161 MPa when soaked in 7.5% glycerol. The drying variation of 80 °C produced a biofilm with the best elasticity of 27.473%. The results of FTIR and EDX analysis confirmed that there were differences in the contents of the modified BC.